Patients’ trajectory from tooth loss to dental rehabilitation and living with implant-supported dentures – a qualitative interview study - Gabriele Müller-Mundt; Philipp-Cornelius Pott; Lara Prinz; Simone Schaumann; Meike Stiesch; Nils Schneider; Franziska A. Herbst (BMC Oral Health)
Abstract Background Since their introduction, implant-supported dentures have gained increasing popularity and are associated with high expectations. Nevertheless, as with other invasive procedures, implant treatment involves post-surgical risks as well as the risk of long-term complications. The present study aimed at exploring patients’ experiences of the entire trajectory of dental implant-treatment, to reach a profound understanding of the patients’ perception of the course of their journey from tooth loss to living with implant-supported dentures. Methods The single-site study employed an exploratory, qualitative design with semi-structured interviews conducted with patients who had received implant-supported dentures for different indications at least one year prior. Thirty-three patients were consecutively recruited by dentists during regular check-ups from March to September 2023 at a German university dental clinic. Interview data were analyzed using deductive-inductive qualitative content analysis. Results Of the 33 patients five patients did not return the consent-to-contact form, and one withdrew their consent, resulting in a final sample of 27 patients (82%). The participants held high expectations regarding the function, durability, and – in cases involving visible tooth gaps – aesthetic outcomes of their implants. Key concerns influencing treatment decisions included the need for bone augmentation and transplantation, age-related factors, and procedural risks. Notwithstanding the lengthy, stepwise nature of the treatment process, the considerable symptom burden, and the high financial cost, most patients considered the implant treatment worthwhile and felt well informed. With one exception the majority of participants (96.3%) reported that their implant-supported dentures functioned and appeared similar to their natural teeth. However, while satisfied with their implant-supported denture, two participants (7.4%) experienced persistent suffering due to temporomandibular disorder and persistent pain following treatment. The issue of prolonged facial pain has arguably been overlooked in aftercare of these patients. Conclusions Dental implants are generally viewed as preferred option for oral rehabilitation. The results underline the importance of comprehensive counselling and after care irrespectively of the complexity of the treatment. While iatrogenic complications and the risk of their chronification are rare, careful attention to these risks remains essential. Further research, encompassing prospective longitudinal studies, is needed, given the risk of recall bias. Clinical trial registration Does not apply.